1988
DOI: 10.1021/la00080a024
|View full text |Cite
|
Sign up to set email alerts
|

Diffusiophoresis of latex particles in electrolyte gradients

Abstract: be related to any physical quantity characterizing the interaction between adsorbates and adsorbents. We inferred

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
177
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(184 citation statements)
references
References 1 publication
6
177
0
1
Order By: Relevance
“…The enhanced colloid transport is not surprising as it has already been reported in a number of studies (7,16,17). However, we have also observed that the density profile of the leading colloids is nonuniform in the lateral direction, and the colloidal particles tend to concentrate as they transport along the channel ( Fig.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…The enhanced colloid transport is not surprising as it has already been reported in a number of studies (7,16,17). However, we have also observed that the density profile of the leading colloids is nonuniform in the lateral direction, and the colloidal particles tend to concentrate as they transport along the channel ( Fig.…”
supporting
confidence: 85%
“…A remarkable fact is that even when κa ≈ 100, unlike electrophoretic mobility (20), the predicted diffusiophoretic mobility deviates noticeably from Γ p ðκa → ∞Þ (10). When κa ≈ 10, which is a general condition for common diffusiophoresis experiments (7,12,16,17), the diffusiophoretic mobility is predicted to be almost an order of magnitude lower, depending on ζ p (10). Our experimental conditions are in a similar range, κa ≈ 2 − 40 [κ −1 = 13.6 nm when c = ðc i + c o Þ=2 ≈ 1 mM], indicating that size effects can be significant.…”
mentioning
confidence: 99%
“…We point to two potential origins of the light-induced chemistry. The light could catalyse a reaction of dissolved species, such as residual water, oxygen, or surfactants such as TBAB at the ITO substrate; these redox reactions would drive a current that would induce an electric field; or, the light-induced ionization of dissolved species, such as TBAB, could create a concentration gradient within the solution, spontaneously setting up an electric field and thereby generating electrodiffusiophoresis 33 . Both mechanisms are consistent with the observation that the photo-induced motion requires illumination of a semiconducting or metallic substrate that is in direct contact with the colloidal solution.…”
Section: Discussionmentioning
confidence: 99%
“…The generality of these findings provides a conceptual picture for understanding, predicting, or designing diffusiophoretic systems. Diffusiophoresis (DP) occurs when colloidal particles are driven into motion by solute concentration gradients [1][2][3]. In recent years, interest in DP has surged, particularly in new contexts such as polymer coating [4], membrane fouling [5,6], enhanced transport of particles into or out of dead-end pores [7,8], self-propelled particles [9,10], and the design of long-range "soluto-inertial" interactions in suspensions [11].…”
Section: Diffusiophoretic Focusing Of Suspended Colloidsmentioning
confidence: 99%